Geometric Partitioning: Explore the Boundary of Optimal Erasure Code Repair - Shan, Yingdi; Chen, Kang; Gong, Tuoyu; Zhou, Lidong; Zhou, Tai; Wu, Yongwei (2021 Symposium on Operating Systems Principles, 2021)
Erasure coding is widely used in building reliable distributed object storage systems despite its high repair cost. Regenerating codes are a special class of erasure codes, which are proposed to minimize the amount of data needed for repair. In this paper, we assess how optimal repair can help to improve object storage systems, and we find that regenerating codes present unique challenges: regenerating codes repair at the granularity of chunks instead of bytes, and the choice of chunk size leads to the tension between streamed degraded read time and repair throughput. To address this dilemma, we propose Geometric Partitioning, which partitions each object into a series of chunks with their sizes in a geometric sequence to obtain the benefits of both large and small chunk sizes. Geometric Partitioning helps regenerating codes to achieve 1.85x recovery performance of RS code while keeping degraded read time low.